2019
DOI: 10.3390/molecules24203743
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Accumulation in the Leaves of the Purple Sweet Potato (Ipomoea batatas L.) Cultivars

Abstract: Sweet potato anthocyanins are water-soluble pigments with many physiological functions. Previous research on anthocyanin accumulation in sweet potato has focused on the roots, but the accumulation progress in the leaves is still unclear. Two purple sweet potato cultivars (Fushu No. 23 and Fushu No. 317) with large quantities of anthocyanin in the leaves were investigated. Anthocyanin composition and content were assessed with ultra-performance liquid chromatography diode-array detection (UPLC-DAD) and ultra-pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 32 publications
(46 reference statements)
1
28
0
1
Order By: Relevance
“…A number of studies about transcriptomics and metabonomics in anthocyanin biosynthesis revealed that the expression levels of structural genes play an important role in anthocyanin accumulation, especially DFR, ANS, and F3H [55][56][57][58]. DFR and ANS are considered as very important enzymes in anthocyanin biosynthesis, as they could direct the flavonoid flux into the anthocyanin branch [55][56][57][58]. Previous studies showed that the expression levels of DFR, ANS, and F3H and some transcription factors were positively correlated with anthocyanin accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies about transcriptomics and metabonomics in anthocyanin biosynthesis revealed that the expression levels of structural genes play an important role in anthocyanin accumulation, especially DFR, ANS, and F3H [55][56][57][58]. DFR and ANS are considered as very important enzymes in anthocyanin biosynthesis, as they could direct the flavonoid flux into the anthocyanin branch [55][56][57][58]. Previous studies showed that the expression levels of DFR, ANS, and F3H and some transcription factors were positively correlated with anthocyanin accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…The main anthocyanin aglycones in I. batatas leaves are cyanidin and peonidin (Islam et al 2002, Li et al 2019. Likewise, in EIBL, cyanidin and peonidin aglycone were also found, dominating the glycosides and their acylated derivatives.…”
Section: Antihyperglycemic and Antioxidant Effect Of Ibl Extractmentioning
confidence: 96%
“…The quantitative reverse transcription PCR (RT-qPCR) was performed to determine the transcript levels of genes using AceQ SYBR qPCR Master Mix (Vazyme Biotech Co., Ltd.) and a real-time PCR system (LightCycler 960, Roche Diagnostics, Basel, Switzerland). The genes for the RT-qPCR amplification were confirmed to be closely related to the regulation of anthocyanin synthesis (Mano et al, 2007;Li et al, 2019;Deng et al, 2020). The primers for these genes were synthesized according to a previous study (Deng et al, 2020) and are listed in Supplementary Table 1.…”
Section: Gene Expression In Different Color Tissues By Quantitative Reverse Transcription Pcr Analysismentioning
confidence: 99%
“…R2R3-MYBs such as IbMYB1 can independently initiate the transcription of anthocyanin biosynthesis genes ( Stracke et al, 2007 ; Dubos et al, 2008 ; Dong, 2014 ; Dong et al, 2014 ) or can interact with other TFs to form the MBW complex to activate anthocyanin biosynthesis in sweet potato and other plants ( Dubos et al, 2008 ; Davies et al, 2012 ; Zhu et al, 2015 ; Deng et al, 2020 ; Yan et al, 2021 ). It has been confirmed that IbMYB1-2 plays a vital regulatory role in anthocyanin accumulation in storage roots ( Tanaka et al, 2011 ), but it is not necessary in all varieties for the expression of IbMYB1 ( Kim et al, 2010 ; Li et al, 2019 ; Zhang et al, 2020 ). A major locus of chromosome 5, where IbMYB1 genes are located, has been shown to have a large effect on the color variation of shoots ( Chen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%